The Effect of etymology elaboration on EFL learners’ comprehension and retention of idioms - Baleghizadeh, Sasan; Bagheri, Mehri Mohammad (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This article reports on a study that investigated the impact of etymological elaboration on EFL students’ comprehension and retention of English idioms. The participants for the study were 32 Iranian upper- intermediate EFL students. They were members of two intact classes randomly assigned to an experimental and a comparison group. The treatment lasted for six two-hour sessions, during each session of which the participants in both groups received five idioms which they were supposed to define. The participants in the experimental group received the idioms along with the pertinent etymological elaborations, while the participants in the comparison group received the same idioms without etymological elaborations. The results revealed that etymological elaboration has a positive effect on EFL students’ comprehension and subsequent retention of idioms.